A SEMANTIC AND PRAGMATIC COMPARISON OF IDIOMATIC EXPRESSIONS REFLECTING THE CONCEPTS OF LABOR AND SUCCESS IN THE ENGLISH AND UZBEK LANGUAGES (International conference on multidisciplinary science, 2026)
This article presents a semantic and pragmatic comparative analysis of idiomatic expressions that reflect the concepts of labour and success in the English and Uzbek languages. Idioms, as culturally marked linguistic units, encode national values, social experience, and collective attitudes toward work, effort, and achievement. The study examines how the concepts of labour and success are conceptualized through idiomatic expressions, focusing on their figurative meaning, evaluative component, and pragmatic function in discourse. Special attention is paid to similarities and differences in metaphorical models, cultural connotations, and communicative usage of idioms in both languages. The analysis reveals that while English idioms tend to emphasize individual effort, competitiveness, and personal achievement, Uzbek idiomatic expressions often reflect collectivism, perseverance, moral integrity, and respect for labour as a social value. The findings contribute to the fields of contrastive linguistics, phraseology, and linguocultural studies, and may be useful for translation studies and intercultural communication.